Alexey Butovsky and the system of physical education in France. - Bubka S.N (Kharkov National Pedagogical University, 2012)
It is presented an analysis of A. Butovsky's views on physical education in France. His position is shown in regard to corporal exercises, in-use in this system (at military and civil educational institutions). The system and practice of the use of such exercises are especially examined for the increase of level of physical preparation of soldiers and officers of the French army. Directions organization of this activity and facilities applied in it are shown. An analysis and generalization of A. Butovsky's different aspects of physical education in schools and other civil educational establishments of France is considered. It is set that activity of A. Butovsky's was in a great deal instrumental in understanding of necessity of the use of corporal exercises. It becomes firmly established that under influence of such useful undertaking at Ministry of the folk inlightening of France Committee was formed for distribution of corporal exercises in education.